PROTOTIPE SISTEM PENDETEKSI POLUSI UDARA MENGGUNAKAN SENSOR ASAP MQ-2, SENSOR GAS MQ-6 DAN SENSOR API PADA RUANGAN DENGAN OUTPUT ALARM BERBASIS MIKROKONTROLLER ARDUINO - Asniati Asniati; Ery Muchyar Hasiri; Wa Ode Rosmiani (JURNAL INFORMATIKA, 2022)
The current industrial development has entered the industrial era 4.0  marked by progress from various aspects, for example the development of microcontroller-based controller technology to be applied to smarthomes. One of them is controlling and monitoring dangerous air pollution and if it is inhaled directly by humans in large enough quantities it will cause health problems in respiratory function. There are various kinds of air pollution, such as CO and CO2 which are found in burning cigarettes or other burning which is carried out every day in households. In addition to hazardous substances, to support a complete smarthome-based research, it is also necessary to add a sensor to detect fires and gas leaks in households. This study aims to design and manufacture a room pollution detector using the MQ-2, MQ-6 and Flame Sensor sensors to detect air pollution caused by CO and CO2 and detect LPG gas leaks and detect fires with notifications via led matrix and based alarms. arduino . The results of this study indicate that to design and manufacture pollution detectors using a smoke sensor that uses Arduino Uno as a microcontroller that controls the work of the system connected to the MQ-2 sensor used to detect smoke, the MQ-6 sensor to detect LPG gas, and to detect fire use Flame. Sensor (Fire Sensor) DFR0076. From the results obtained by the MQ2 smoke sensor, the resistance value of the sensor will decrease when smoke is given, otherwise the sensor resistance value will increase when smoke is not given. The sensor resistance ranges from 150 Ω – 300 Ω when smoked and 1.5 KΩ to 1.7 KΩ when not smoked. gas sensor resistance increases when given gas and decreases when it does not detect gas. The sensor resistance when reading the presence of gas in the air is between 100 Ω - 400 Ω, and when it does not detect gas, it is 0 Ω - 12 Ω. On the Flame sensor, the sensor voltage value changes when it detects fire. The voltage value increases if it detects fire and vice versa the sensor voltage decreases when it does not detect fire. The sensor voltage value when detecting fire is between 1.2 Volts – 5 Volts, while when it does not detect fire, it is between 0 Volts – 0.9 Volts.